Sustainable Horticulture, Volume 2 : Food, Health, and Nutrition - Mandal, Debashis; Shukla, Amritesh C.; Siddiqui, Mohammed Wasim (Apple Academic Press, 2018)
"Sustainable Horticulture, Volume 2: Food, Health, and Nutrition addresses some of the most important topics facing horticulture around the world today. This volume, part of the two-volume compendium, focuses on research trends in sustainable horticulture that include postharvest management and processed food production from horticulture crops, crop protection and plant health management, and horticulture for human health and nutrition. Global food demand is expected to be double by 2050, while at the same time the production environment and natural resources are continually shrinking and deteriorating due to many complex factors. Horticulture, a major sector of agriculture, is vital to enhancing crop production and productivity in parity with agricultural crops to meet the emerging food demand. Implementing sustainable models of crop production is really an enormous endeavor. Promising technologies and management options are needed to increase productivity to meet the growing food demand despite deteriorating production environments. The book is divided into sections covering: Postharvest Management and Processed FoodProtection of Horticulture CropsHorticulture for Health and NutritionTogether with volume 1 (Volume 1: Diversity, Production, and Crop Improvement), this two-volume compendium presents an abundance of new research on sustainable horticulture that will be valuable for a broad audience, including students of horticulture, faculty and instructors, scientists, agriculturists, government and nongovernmental organizations, and other industry professionals."--Provided by publisher.
CHAPTER 15 INTEGRATED HEALTH MANAGEMENTIN HORTICULTURAL CROPS C. CHATTOPADHYAY1 and AJANTA BIRAH2CHAPTER 16 TECHNOLOGY FOR DIAGNOSIS OFPLANT VIRUSES IN HORTICULTURALCROPS IN INDIA BIKASH MANDAL; CHAPTER 17ACARICIDAL ACTIVITY OFPETROLEUM ETHER EXTRACT FROMSEED OF CUSTARD APPLE, ANNONASQUAMOSA L. (ANNONACEAE)AGAINST RED SPIDER MITE,OLIGONYCHUS COFFEAE (NIETNER)INFESTING TEA BIPLAB TUDU and SIBDAS BASKEY; CHAPTER 18EVALUATION OF SOME PLANTEXTRACTS AGAINST EARLY BLIGHTOF TOMATO UNDER NET HOUSECONDITION MANISHA DUBEY, T. S. THIND, S. K. JINDAL, and R. K. DUBEY
OCLC-licensed vendor bibliographic record.
Keywords: TECHNOLOGY & ENGINEERING / Agriculture / General; Sustainable horticulture